(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
As time changes, the Internet of Things (IoT) describes a network of physical objects that manages all the essential human needs in urban areas. The researchers decided to innovate an IoT Controller for a Smart Bicycle, which is an IoT Bicycle Speedometer and Tail Light with Anti-Theft Alarm GPS and SMS Notification Security System, which is IoT-based with sensors and modules. The main goal of this research is to aid them in being safe, preventing stolen bicycles, and tracking their speed in real time by using their smartphone. The results after testing: when the cyclist opens the device, the cyclist will hear a beep code; the first Beep is for Wi-Fi Connected, the Second beep for Blynk Connected, the Double beep for SMS Notification, and the last is a triple beep for IR proximity sensor and all components are ready to function and manually controlled via Blynk application. Also, when the prototype is triggered, the GSM module will send a message to the user containing the GPS location. In sound alarm results, 1m is around 95dB, and 5 meters is 82 dB. The battery capacity is 3000mA, with a 2-hour and 31-minute life duration at 3.7V. The rechargeable battery is the main power source. The evaluation of the survey shows that respondents agree with the proposed prototype. The technologies used were compatible with the microcontroller, such as ESP32s, and showed success in the operation of the prototype. It contains a GPS module to track the location of the bicycle using a smartphone and also an anti-theft alarm for security features to ensure the bicycle is safe. Therefore, it is concluded that the ESP32s microcontroller is an effective electronic gadget to fabricate a prototype IOT Bicycle Speedometer and Tail Light Signal with an anti-theft alarm GPS and SMS Notification Security System.